Gluten-Free Autochthonous Foodstuff (South America and Other Countries) - García, María Alejandra (2015)
The conservation and sustainable use of biodiversity for agriculture and nutrition have been extensively pointed out as crucial elements for food security and nutrition. Likewise, the relevance of learning from traditional foods and applying indigenous knowledge for the development and production of innovative gluten-free foods has been referred. South and Central America have supplied a great quantity of plant foods for the sustenance of the humankind. Latin-America is by this time one of the World largest net food exporting area. However, its complete potential to expand agricultural production for regional consumption and global export has not yet been achieved. The region has a large number of skilled farmers that have preserved and transmitted their knowledge through generations. Feeding a rapidly growing global population without expanding farming into environmentally susceptible areas and reducing the productive ability of the land already cultivated is a challenge that presents an elevated complexity level. In a framework of a strong need for diet diversification, populations with special nutritional requirements, such as celiac patients, should be benefited with the offer of more balanced, rich and safe diet components. The possibility of learning to a great extent from traditional foods and spread on local and territorial knowledge for the development and production of innovative gluten-free foods appears as a promising alternative. This chapter collects information about several plant species from the American continent that are more extensively used for the production of gluten-free foods (e. g. maize, potato, cassava, sweet potato, quinoa, amaranth, some legume grains) as well as other species that could potentially be developed with the same purpose, such as the Andean root and tuber crops: achira, ahipa, arracacha, maca, mashua, mauka, oca, ulluco, and yacon.